2023
DOI: 10.3390/biology12010124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Football Simulated Exercise on Injury Risk Factors for Anterior Cruciate Ligament (ACL) Injury in Amateur Female Players

Abstract: Females are more at risk of Anterior Cruciate Ligament (ACL) injuries than males; however, there is limited literature on neuromuscular risk factors such as angle-specific hamstring/quadriceps functional strength ratios (Hecc/Qcon) and rate of torque development (RTD) in female footballers. The aim of this study was to investigate the effects of fatigue on these neuromuscular risk factors. Thirty-three amateur players (20.3 ± 2.0 years old, 1.67 ± 9.31 m, 63.4 ±8.1 kg, 23.6 ± 5.7% body fat) performed strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…The mean match time was similar to the half-time of a football match and allowed for inferences about submaximal effort, as suggested by a previous study [ 36 ].…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The mean match time was similar to the half-time of a football match and allowed for inferences about submaximal effort, as suggested by a previous study [ 36 ].…”
Section: Resultssupporting
confidence: 73%
“…Play time has therefore been assumed to be a gross indicator of player quality [ 34 ]. A previous study showed an increase in Borg’s perceived exertion of +25% [ 36 ] after a match. It has been suggested that studies considering half-match duration (45 min) can be used to better understand the performance/fatigue relationships of female soccer players [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies are required to understand the role of gender on patellar instability rates and risk factors. Besides gender, leg dominance has shown to affect the rate of knee injuries in previous studies [11,20]. Though we did not study leg dominance in particular, there were no differences in risk factors between left and right knees (Table 2).…”
Section: Discussionmentioning
confidence: 79%
“…RTD extends our capacity to evaluate the maximal force-generating capacity and plays a pivotal role in activities requiring quick muscle contractions and short-duration execution, such as jumping, sprinting, or weightlifting [13][14][15][16][17], as it reflects the muscles' capability to swiftly generate force during the very initial phase of muscle contraction [1,2]. Also, RTD is often associated with enhanced athletic performance, injury prevention, and return to sport readiness [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%